Addressing Challenging Behavior: Considering the Logic of Probability. (May 2014) - Scott, Terrance M.; Hirn, Regina G.
When dealing with children who exhibit challenging behaviors there are no known interventions that work for all students or at all times. Thus, intervention for these students is often implemented in a trial and error manner. This article provides a logic for considering probability as a factor in selecting strategies. Understanding that some interventions are more likely to work than others and the fact that adult behavior is the main impetus for change in student behavior, the key is in considering which teacher behaviors offer the highest probability of student success. Suggestions and examples are provided.